(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
India and the USA are having an unprecedented warmness in their relationship presently. After all the hindrances and hiccups, the two largest Democracies are finally engaged optimally in economic and trade activities. Simultaneously, India is also developing fruitful relationship with East Asian countries and the present government has evolved the Indian foreign policy from “Look East “to “Act East”. However, this Act east policy need not to be seen in isolation and it has to be seen as a strategic alliance between India, USA, and east Asian countries to neutralize the strategically and economic advancement of China as the global economic superpower. This closeness is unprecedented, however it should not be subjected to the sovereignty of the Indian foreign policy and India should remain Non-aligned as it has reaped humongous benefits by being non-partisan.